6954 Effect Of The SARS-CoV-2 Pandemic on Metabolic Control In Patients With Type 2 Diabetes: A 5-year Cohort Follow-Up - Morales Rodríguez, Devany Paola; Romero Ibarguengoitia, Maria Elena; Garza-Silva, Arnulfo; Rivera-Cavazos, Andrea; Fernandez-Chau, Iván Francisco; Cepeda Medina, Andrea Belinda; Gonzalez-Cantú, Arnulfo (Journal of the Endocrine Society, 2024)
Abstract Disclosure: D.P. Morales Rodríguez: None. M. Romero Ibarguengoitia: None. A. Garza-Silva: None. A. Rivera-Cavazos: None. I. Fernandez-Chau: None. A. Cepeda Medina: None. A. Gonzalez-Cantú: None. The SARS-CoV-2 pandemic brought a radical shift in the healthcare system and a suboptimal care for vulnerable patients, such as those with Type 2 Diabetes Mellitus (T2DM). Thus, we compared the metabolic control of patients with T2DM before and throughout 3 years of the SARS-CoV-2 pandemic, described the type of consultations and trends in attendance in various specialties, and compared the number of medications prescribed to patients before and during the pandemic. We conducted a retrospective observational cohort study on steelworkers with T2DM from a hospital in northeastern Mexico, who were treated by a multidisciplinary team from 2018 to 2022. We analyzed HbA1C levels, fasting serum glucose (FGS), low-density lipoprotein cholesterol (LDLc), blood pressure (BP) values, microalbuminuria, attendance at consultations across different specialties, and the trend in medication usage. We analyzed 999 subjects, 516 (51.7%) males, with a mean age (SD) of 60.1 (12.7) years. A significant difference was found in the proportion of controlled patients based on HbA1C with 55.5% in 2018 and 70.7% in 2022 (p<0.001). There was an increase of FGS control from 13.8% in 2018 to 56.1% in 2022 (p<0.001). LDL cholesterol control exhibited a decrease from 62.1% in 2018 to 57% in 2022 (p<0.001). Proportion of patients with systolic BP control decreased from 82.7% in 2018 to 80.1% in 2022 (p<0.001). Diastolic BP control was 89.6% in 2018 with an increase to 91.4% in 2022 (p=0.01). Microalbuminuria based control, increased from 80.5% in 2018 to 89% in 2022 (p=0.002). Telephone consultations were introduced in 2020, with 899 (90%) patients using this modality at least once, leading to a 35.8% decrease of in-person consultations (n=541,54.2%) and reaching its lowest point in 2021 (n=2, 0.2%). Throughout the follow-up period, all patients had at least one annual consultation with an internist or geriatrician based on their age group. There was an increase of endocrinology consultations from 8.5% in 2018 to 12.1% in 2022 and in cardiology from 6.9% in 2018 to 10.3% in 2022 (<0.05). There was a rise in the prescription of oral hypoglycemic agents raging from 4.9% to 14.2% between 2018 and 2020, with SGLT2 inhibitors being the highest prescribed and a 2.5% decrease in the prescription of sulfonylureas between 2018 and 2020. Similarly, there was an increase in the prescription of long-acting insulin by 5.9% between 2018 and 2020. There was a higher proportion of patients with controlled glycemic and diastolic blood pressure targets during the SARS-CoV-2 pandemic, this can be attributed to patient’s access to telemedicine and a multidisciplinary team capable of providing an appropriate medication prescription for an optimized management and improvement in patient’s quality of life. Presentation: 6/1/2024